An investigation of active safety control strategies for improving the lateral stability of car-trailer systems. (4th February 2020) - Zhao, Lin; He, Yuping
This paper presents an evaluation of control strategies for improving the lateral stability of car-trailer systems. A linear stability analysis method is proposed for the evaluation. The strategies include active trailer differential braking, active trailer steering and variable geometry approach. A linear 3 degrees of freedom (DOF) yaw-plane car-trailer model is generated for the controllers' design and a nonlinear 21-DOF yaw-roll car-trailer model is developed in CarSim to validate the stability control strategies by means of numerical simulations. To determine the stable motion boundary, eigenvalue analysis is conducted for identifying the vehicle critical speed. The linear quadratic regulator technique is applied to the design of controllers for active trailer braking, active trailer steering and variable geometry strategies. It is revealed that the active trailer braking strategy is feasible and effective for improving the lateral stability of car-trailer systems. Simulation results demonstrate the effectiveness of the linear stability analysis method.